2007
DOI: 10.1007/s12020-007-9026-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of cystic fibrosis transmembrane conductance regulator in the rat endocrine pancreas

Abstract: Impaired glucose tolerance and overt diabetes mellitus are becoming increasingly common complications of cystic fibrosis (CF), most probably merely as a result of increased life expectancy. In order to understand the pathophysiology of cystic fibrosis-related diabetes (CFRD), knowledge on the possible expression and cell distribution of the cystic fibrosis transmembrane conductance regulator (CFTR) protein within the endocrine pancreas is required. In this report, we establish the first evidence for expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 32 publications
0
52
2
Order By: Relevance
“…CFRD results more from decreased ␤-cell function than from decreased insulin sensitivity (19). This finding supports a function for CFTR in pancreatic islets where, in rats, investigators have identified CFTR mRNA (20). In mice made diabetic by streptozotocin, those who were CFTR-null (Ϫ/Ϫ) had higher blood glucose levels than other mice; the investigators concluded that islet dysfunction is inherent to the CFTR Ϫ/Ϫ state (21).…”
Section: Risk Factorsmentioning
confidence: 72%
“…CFRD results more from decreased ␤-cell function than from decreased insulin sensitivity (19). This finding supports a function for CFTR in pancreatic islets where, in rats, investigators have identified CFTR mRNA (20). In mice made diabetic by streptozotocin, those who were CFTR-null (Ϫ/Ϫ) had higher blood glucose levels than other mice; the investigators concluded that islet dysfunction is inherent to the CFTR Ϫ/Ϫ state (21).…”
Section: Risk Factorsmentioning
confidence: 72%
“…Recent data suggest there may be an intrinsic defect in b-cell function in CF. CFTR is expressed in human and mouse pancreatic a and b cells, and CFTR conductance has been measured in mouse b cells (24,25). Whether CFTR plays a role in insulin secretion is unknown.…”
Section: Original Articlementioning
confidence: 99%
“…Impaired insulin secretion " CFTR protein is expressed in a-cells and b-cells in the rat pancreas, although its role in these cells is not well known (44). Evidence reveals a role of CFTR in glucose-induced electrical activities and insulin secretion in b-cells (45).…”
Section: B-cell-specific Dysfunctionmentioning
confidence: 99%